Outcomes in coeliac disease: a qualitative exploration of patients' views on what they want to achieve when seeing a dietitian. Issue 5 (16th May 2016) - Madden, A. M.; Riordan, A. M.; Knowles, L.
Abstract: Background: Coeliac disease (CD) is managed by life‐long adherence to a gluten‐free diet and dietitians have the potential to facilitate this. Patient involvement through shared decision‐making is central to behaviour‐change skills used by dietitians, although there is little evidence supporting its inclusion in evaluating dietetic interventions. The present study aimed to explore patients' preferences for diet and nutrition‐related outcomes in CD. Methods: Adults with CD or adult carers of children with CD were invited through support networks. Participants took part in a telephone, face‐to‐face interview or focus group which was audio‐recorded and transcribed. Themes were developed using a framework method. Ethical approval was obtained. Results: Twenty‐nine adult patients and five parents of CD children participated 0–34 years after diagnosis. Four main outcome‐related themes emerged: (i) Participants wanted information specific to their lifestyle and time since diagnosis, focussing on food containing gluten, practical issues, prescribable items and general nutrition. (ii) The degree of satisfaction with the consultation process impacted on participants' experience, including the dietitian's CD expertise, consistency of the dietitian seen, and the frequency and length of appointments. (iii) Health concerns were important to participants and focussed on risk of osteoporosis, unwanted weight gain, and the fat and sugar content of manufactured gluten‐free products. (iv) Clinical monitoring, including bone scans and antibody measurements, was mentioned but was not described as being of importance for most participants. Conclusions: The outcomes preferred by CD patients and carers focussed primarily on information and resources received and satisfaction with their dietetic consultation.